SLC4A11 is a targetable marker correlated with therapeutic responses in ovarian cancer - Xin Li; Jia Yuan; Fanchen Wang; Bin Guan; Wencai Guan; Jimin Shi; Qi Lu; Jihong Zhang; Guoxiong Xu (Journal of Ovarian Research)
Abstract Background Solute carrier family 4 member 11 (SLC4A11) is involved in borate homeostasis, metabolism reprogramming, cell growth, and cell adhesion. However, the biological function of SLC4A11 in ovarian cancer (OC) is still unclear. This study explores the anti-tumor and biological activities of SLC4A11 in OC. Methods The expression and function of SLC4A11 were evaluated in human OC cells and xenograft mice. SLC4A11 expression was evaluated using data from the TCGA-OV, GTEx, and GEO datasets. The genetic status of SLC4A11 was analyzed by the cBioPortal database. The data of expressional abundance, immunochemistry, and immunofluorescence were analyzed through the HPA database. The correlation between SLC4A11 and immune responses was analyzed with the CIBERSORT database, whereas therapeutic responses were analyzed with the CellMiner database. Results SLC4A11 was found to be highly expressed in OC tissues/cells and had a relationship with an unfavorable prognosis in patients with OC. The overexpressed SLC4A11 promoted OC cell proliferation, migration, and invasion. Reducing SLC4A11 caused the cell cycle arrest at the G0/G1 phase and triggered apoptosis. The in vivo study with a xenographic model revealed that the knockdown of SLC4A11 suppressed tumor growth. Subsequent bioinformatics analyses revealed that SLC4A11 expression was associated with immune responses and therapeutic drug sensitivity. Conclusions These findings have illustrated the oncogenic role of SLC4A11 in OC. SLC4A11 is overexpressed and is correlated with poor prognosis in OC. SLC4A11 may be a targetable biomarker and has a potential value of application in treating patients with OC.